Implementation of The Ventilator Associated Pneumonia Bundle in the Intensive Care Unit - Fiatun, Fransisca Danik; I Komang Widarma Atmaja; Ni Luh Kompiang Ariani (Nursing and Health Sciences Journal (NHSJ), 2024)
Ventilator is a medical used to help patients to breath in the Intensive Care Unit (ICU). Patients with ventilator are at risk of experiencing Ventilator Associated Pneumonia (VAP). VAP is one of the Health Care Associated Infections. VAP contributes to the morbidity and mortality of patients treated in the ICU. One of the efforts to prevent and control VAP is to implement a VAP bundle. This study aims to describe the implementation of the VAP bundle in the ICU in July-September 2022. This type of research is descriptive analytic which describes the application of the VAP bundle in ICU, used purposive sampling with inclusion criteria of patients who had used a ventilator for more than 48 hours and did not experience pneumonia at the first time they were put on ventilator. The research sample obtained was 30 respondents. The results of the study showed that 50% of respondent were in the age range of 50-59 years old, 60% were female and 66.7% were a post-surgical patient. The implementation of hand hygiene was 86.7%, the implementation of head up 30-45 was 96.7%, the implementation of giving peptic ulcer disease prophylaxis was 93.3% and the implementation of giving deep vein thrombosis prophylaxis was 26.7%. VAP in July-September still occurs. The average VAP incidence rate in July-September 2022 is 2.53‰. Conclusions and recommendations, the VAP bundle has been implemented in the ICU, progressing but not yet optimal, efforts to prevent VAP are needed.